«La nit»: sobre algunes constants de Vicent Andrés Estellés - Ballester, Josep (Caplletra. Revista Internacional de Filologia, 2015)
The study focuses on Estellés work during the fifties, his beginnings, and specially his book of poems La nit. It analyses the resources and constants which appear in the book and define part of the poetry of the Valencian poet from Burjassot.